1998
DOI: 10.1161/01.cir.98.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Increased QT Dispersion in Patients With Vasospastic Angina

Abstract: Patients with vasospastic angina exhibited an increased baseline QTc dispersion compared with patients with atypical chest pain, which suggests that inhomogeneity of repolarization and susceptibility to ventricular arrhythmias are increased in patients with vasospastic angina, even when asymptomatic. The association between increased QTc dispersion and ventricular arrhythmias during the provocation test suggests that measurement of QT dispersion may help predict which patients with vasospastic angina are at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 44 publications
2
49
0
1
Order By: Relevance
“…[7][8][9] In the present study, 4 cases of polymorphic VT showed a pattern of torsade de pointes, which was frequently encountered in the presence of a prolonged QT interval. The polymorphic VT with a torsade de pointes pattern was infrequently noted with normal Q-T interval in the early stage of an acute myocardial infarction.…”
Section: Possible Mechanism Of Spontaneous Polymorphic Vt During Corosupporting
confidence: 50%
See 1 more Smart Citation
“…[7][8][9] In the present study, 4 cases of polymorphic VT showed a pattern of torsade de pointes, which was frequently encountered in the presence of a prolonged QT interval. The polymorphic VT with a torsade de pointes pattern was infrequently noted with normal Q-T interval in the early stage of an acute myocardial infarction.…”
Section: Possible Mechanism Of Spontaneous Polymorphic Vt During Corosupporting
confidence: 50%
“…8 Here we evaluated ventricular vulnerability by programmed ventricular stimulation in 5 patients with spontaneous VT at baseline who did not have any sign of myocardial ischemia. Consequently, polymorphic VT was induced in 2 of the 5 patients, with 1 patient developing ventricular fibrillation.…”
Section: Possible Mechanism Of Spontaneous Polymorphic Vt During Coromentioning
confidence: 99%
“…QT dispersion and cardiac disease: Increased QT dispersion reflects electrical inhomogeneity, which may occur as a result of myocardial ischemia, mitral valve prolapse, ventricular hypertrophy or dilatation, autonomic neuropathy, peripheral vascular disease, and hypertension. [9][10][11][12][13][14][15] A recent study, which analyzed the 12-lead electrocardiograms of 1501 healthy adults and 1784 healthy children found that QTd was age and sex independent.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with vasospastic angina, it was found that QTc dispersion was increased and this was associated with ventricular arrhythmias. 9) In a study of 182 patients with non-insulin dependent diabetes mellitus, QTd, QTcd, and QTc max were reported to be accurate predictors of cardiac death. 17) None of our subjects had overt diabetes mellitus (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…16 In the present study, all subjects were subjected to coronary angiography and were diagnosed as having no significant coronary artery stenosis. Moreover, the possibility of vasospastic angina was ruled out on the results of the methylergometrine maleate test.…”
Section: Discussionmentioning
confidence: 99%